Використання софістичних прийомів у публічному виступі та суперечці - Деркач, У. Ю. (ХНУРЕ, 2023)
Sophists were not limited in their speeches only to topics in which they were aware. For them, there were no topics they could not dispute, because their skill reached such a level that they were able to talk about completely unknown things to them and still impress upon listeners and the opponent. The Sophist rhetoricians did not focus on identifying the truth, but the most important thing for them was to prove their case.